Bien Vivir, uma metáfora que libera a experiência sensível dos Direitos Coletivos na Saúde - Paulo Henrique Martins (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
To deeper the understanding of the epistemic limits of capitalism materialist consumption utopia inspiring dominant models of development, on one hand, and the emergence of anti-colonial reactions in progress, on the other one, we consider important to meditate on the emergence of new sensibilities about life that is occuring in Latin America and, in particular, in Bolivia. These cognitive, affective, moral and political sensibilities are reflecting on new collective human rights inspiring new meaning on commons goods, social justice and egalitarianism. The Bolivian’s case is adequate for this thinking because it contributes to reframe the meanings of health from other understandings of the relationship between Human Being and Nature. The metaphor of Vivir Bien has practical and political value that should be the object of enlarged understanding by those who are concerned about the anticolonial critical perspectives.